Gastroprotective, Toxicological And Immunotoxicological Evaluation Of Austroplenckia Populnea - F.H. MELO,; R.M. CENACCHI,; J.P. BARBOSA,; G.D.F. SILVA,; S.A. VIEIRA FILHO,; T.M.D.P. GUIMARÃES,; V.P.C.P. TOLEDO,; A.M.D. BARROS,; G.L. ARAUJO,; C.A. TAGLIATI, (International Journal of Pharma and Bio Sciences, 2012)
Austroplenckia populnea (Celastraceae), is used popularly in Brazil as anti-dysenteric. However, antispermatogenic and gastric protective activity were observed. The objective of the present study was the evaluation of the gastroprotective activity, toxicity and immunotoxicity of the ethanol extract of A. populnea in rodents. Doses of 1000 and 2000 mg/kg were utilized in the sub-acute toxicity and immunotoxicological tests. No alterations in the behavior, body weight or consumption of water and ration were detected. A few alterations in the hematological parameters, were observed, such as biochemical ones, which decreased or remained constant, but without clinical significance. There was a discrete variation in the hyper-reactivity of the white splenic pulp in the histopathological evaluation. A modulation of the humoral immune response was observed in the immunotoxicological evaluation, but without interference in the cellular immune response. Considering the results obtained, it is believed that the continuation of the study of this extract is justifiable.